Confidential 86/12-I a. 70 Petroleum Concessions Limited. Muscat - Skliros, John; Longrigg, Stephen Hemsley; Lewisohn, Frederick; Holmes, Frank (British Library, 1936)
The volume contains correspondence between the Political Resident in the Persian Gulf (Trenchard Craven Fowle), the Political Agent at Bahrain (Percy Gordon Loch), the Political Agent at Muscat (Ralph Ponsonby Watts), the India Office (Maurice Clauson), Petroleum Concessions Limited (Major Frank Holmes, John Skliros, Stephen Hemsley Longrigg) and the Standard Oil Company of California (Hamilton R Ballantyne) regarding Petroleum Concessions Limited’s interest in an oil concession in Muscat and their intention of opening negotiations with the Sultan of Muscat and Oman (Sayyid Sa‘īd bin Taymūr Āl Bū Sa‘īd) which were delayed owing to the Sultan extending his stay in the interior of his country near Dhofar [Zufār]. Included in the file are copies in Arabic and English of the proposed concession agreement for Muscat and Oman, including correspondence regarding possible amendments to the agreement and copies of the various drafts which can be found at folios 5-20, 28-40, 109-124, 136-139, 144-159 and 195-210.Also discussed is correspondence between the Sultan of Muscat and the Standard Oil Company of California, including samples of oil seepages found near Dhofar which were sent to the company for assessment but were not found to contain crude oil. Also discussed are the concerns of British authorities at Standard Oil’s attempts to acquire concessions in the Persian Gulf and conversations between the Company’s representative in London and the India Office at which the Company were made aware that Petroleum Concessions Limited had been given first right of negotiation in that area.Other matters of interest within the file include: concerns over possible reactions by the Bani Bu Ali [Banī Bū ‘Alī] tribe to any negotiations for, or grant of, an oil concession in Muscat, which would cover the Sur district where they held power; discussion regarding the difficulty of defining the boundaries for the Imamate of Oman; a visit paid by Major Holmes to Cairo and the British authorities in the Persian Gulf interest in knowing who he had met and what he had discussed whilst there; correspondence regarding Count Byron de Prorok and his wife Alice who had travelled from Aden to Muscat and Bahrain with the intention of searching for antiquities and archaeological sites in the region, and Tullio Pastori who was visiting Muscat and Bandar Abbas [Bandar-e ʻAbbās] to recruit labour for an Italian road construction project in Eritrea; and British officials suspicions that their visits to the area were on behalf of an Italian Oil concern, which were concluded to be unfounded. A series of file notes which were maintained as a record of the correspondence in the volume can be found at folios 227-236.
Keywords: Vie politique -- Oman -- 1932-1970

File XVII/2 Government Property, Christian Cemeteries - Dykstra, Dirk (1936)
This file contains correspondence related to the maintenance and condition of the three Christian (or European) cemeteries in Muscat. The majority of the correspondence in the file is internal correspondence between British officials, but the file also contains correspondence between the Political Agency in Muscat and external entities including a contractor in India (concerning the purchase of chain for use as railing in a cemetery); Dirk Dykstra of the American Mission in Muscat; and the Ministry [naẓārah] of Foreign Affairs of the Sultanate of Muscat and Oman. The correspondence with the Ministry of Foreign Affairs relates to a stolen tombstone being used as flooring in a residence near Matrah, two of these letters are in Arabic (accompanied by English translations). In addition to correspondence, the file contains a plan of the Catholic Cemetery near the American Mission in Muscat (folio 16).
Keywords: Christianisme -- Oman

الدليل الواضح في الرد على من اجاز العمل بالتيليفون في الصوم والافطار - بن الحاج, ابراهيم بن الحاج موسى (1936)
Keywords: Fiqh; Fiqh -- Traité

Deux récits de voyage inédits en Afrique du Nord au XVe siècle - Ibn Halil, Abdalbasit; Adorne, Anselme (Larose, 1936)
Keywords: Récits de voyage -- Djerba

al-Ṣawm bi’l-Talifūn wa’l-Talghrāf - Iṭfayyish, Abū Isḥāq Ibrāhīm (al-Maṭb. al-Salafiyya, 1936)
Keywords: Pratiques rituelles

Les douces beautés de la Tunisie - Mauclair, Camille (Editions Bernard Grasset, 1936)
Keywords: Récits de voyage -- Djerba

Oasis du Sahara: voyage aux villes du Mzab - Papy, Louis (impr. E. Taffard, 1936)
Keywords: Récits de voyage -- Mzab

Au M'zab: désert dans le désert... - Gers, José (Librairie de l'Oeuvre Saint-Charles, 1936)
Keywords: Récits de voyage -- Mzab